PENGGUNAAN MULTIMEDIA INTERAKTIF DALAM UPAYA MENINGKATKAN KEMAMPUAN MENARIKAAN TARI GUNA WIDYA DHARMA RAKSAKA PADA KEGIATAN EKSTRAKURIKULER TARI SISWA SMA NEGERI 1 BLAHBATUH TAHUN PELAJARAN 2020/2021 - I Made Gede Putra Wijaya; I Kadek Agus Ariana (Widyadari : Jurnal Pendidikan, 2021)
This study aimed to determine whether interactive multimedia can improve the student's dancing ability of Guna Widya Dharma Raksaka dance, and student responses to the dance extracurricular activities for students at SMA Negeri 1 Blahbatuh, Gianyar, for the academic year of 2020/2021. This study used classroom action research with one cycle and has four stages, namely planning, implementing actions, observing and reflecting. The setting of this research was consisting of two, which were the setting of place and time. The setting of place of this research was at SMA Negeri 1 Blahbatuh, which located at Jalan Astina Jaya Blahbatuh, Gianyar. The setting of time of this research was in the even (second) semester of the academic year of 2020/2021. In order to obtaining the data, the researcher used the test and observation method. The test method that is used is an action test. Meanwhile, the method of processing the data that is used in this research was the method in the form of descriptive statistics. The results of this research showed that the average score of the students was 64.62% in the initial observation. Meanwhile, it was increased after using interactive multimedia in the first cycle, with an average value of 70.62. Thus, showed that 40 students who took part in the dance extracurriculars at SMA Negeri 1 Blahbatuh, Gianyar in the academic year of 2020/2021 can be declared as well completed. It can be concluded that the use of interactive multimedia can increase the student responses in order to improve the dancing skills of Widya Dharma Raksaka dance, of the dance extracurricular activities for the students at SMA Negeri 1 Blahbatuh, Gianyar, for the academic year of 2020/2021. As shown in the pre-cycle, the average was 63.12 and in the first cycle the average student response was increased into 71.12. It means that the use of the interactive multimedia to increase student response can be well accepted in order to improve the dancing skills for Widya Dharma Raksaka dance, of the dance extracurricular activities of the students at SMA Negeri 1 Blahbatuh, Gianyar, for the academic year of 2020/2021.